Quantitative methods to analyze the severe obesity in Romania and its impact over public administration health expenditures - Cătălina Liliana ANDREI; Ruxandra Diana SINESCU; Claudiu HERȚELIU; Andreea MIRICĂ (Transylvanian Review of Administrative Sciences, 2018)
In this article we present the situation of the Romanian population suffering from severe obesity (measured using BMI), focusing on specific situations with regard to age, gender, residence, development region or educational level. The main dataset used for the current paper is extracted from the Romanian Report for 2008 European Health Interview Survey (EHIS). The sample (a representative one) consists of more than 10,000 randomly selected households. Also, the article shows the consequences of this economic and social state especially for people who have been forced to seek surgical treatment. All financial estimates regarding the obesity burden are produced at country level.